Simulation of spatial-temporal chaos: The simplest mathematical patterns and computer graphics - Romanenko, Ye. Yu.; Vereikina, M. B. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
The article presents three scenarios of the evolution of spatial-temporal chaos and specifies the corresponding types of chaotic solutions to a certain nonlinear boundary-value problem for PDE. Analytic assertions are illustrated by numerical analysis and computer graphics.